Short birth interval as a risk factor for ductal breast carcinoma in patients from northern Peru - Murgia-Flores, Amalia (2021)
Background: Breast cancer is the most common histological type and it is a frequent cause of death in Peruvian women. Objective: To demonstrate that birth interval is a risk factor for ductal breast carcinoma. Material and Methods: This case-control study included 304 Peruvian women with histological diagnosis of breast carcinoma. They were divided into two groups, one with ductal carcinoma and another with non-ductal carcinoma (control). Besides birth interval; parity, age at first delivery, age at last delivery, age at histological diagnosis, interval from last delivery to diagnosis and molecular subtype were also evaluated. Results: The frequency of Ductal breast cancer was 78% in patients with short birth interval. The ratio between presence of short birth interval versus absence of short birth interval is 1.86 times higher in ductal breast cancer patients (CI 95%: 1,12-3,08). Additionally, there was significant association in age at first delivery ≤ 20 years (p<0,001) and interval from last delivery to diagnosis >10 years (p<0,001). Conclusion: short birth interval is a risk factor for ductal breast cancer, which can also be modified and used as a prevention element, so it should be included in the medicalrecord.